CRIMINAL LIABILITY, AMNESTY, AND PARDON IN THE SYSTEM OF MODERN CRIMINAL LAW POLICY: THEORETICAL FOUNDATIONS, PRACTICE, AND PROSPECTS - Shkola , Serhii (Collection of scientific papers «ΛΌГOΣ», 2025)
Criminal liability is a core category of criminal law, reflecting the state’s legal response to a committed offense. It encompasses both the establishment of guilt and the imposition or non-imposition of legal consequences. This concept is closely linked to mechanisms of exemption from liability and to incentive-based legal provisions.